1970
DOI: 10.1073/pnas.65.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Microtubule Protein from Cultured Mouse Neuroblastoma Cells

Abstract: Abstract. The addition of vinblastine to high-speed supernatants derived from homogenates of cultured mouse neuroblastoma cells results in the formation of a precipitate which has been characterized as microtubule protein by the following criteria: colchicine-binding activity, molecular weight, amino acid composition, and electrophoretic mobility. The method therefore permits the rapid isolation of microtubule protein from crude supernatants of neuroblastoma cells.Recent work has shown that the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

1970
1970
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(135 citation statements)
references
References 17 publications
4
131
0
Order By: Relevance
“…In our studies with platelets we have found that the more conventional procedures for tubulin isolation based upon ammonium sulphate fractionation and DEAE-ion exchange chromatography [ IO,1 3] were inapplicable and gave poor yields of tubulin with large amounts of actin. Similarly, the use of the Vinca alkaloid, Vinblastine sulphate to precipitate tubulin from the platelet soluble phase, (a technique sometimes used to isolate tubulin from other sources [29] ) resulted in very impure preparations in which actin again predominated.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies with platelets we have found that the more conventional procedures for tubulin isolation based upon ammonium sulphate fractionation and DEAE-ion exchange chromatography [ IO,1 3] were inapplicable and gave poor yields of tubulin with large amounts of actin. Similarly, the use of the Vinca alkaloid, Vinblastine sulphate to precipitate tubulin from the platelet soluble phase, (a technique sometimes used to isolate tubulin from other sources [29] ) resulted in very impure preparations in which actin again predominated.…”
Section: Discussionmentioning
confidence: 99%
“…5) that nearly 50 % of the 32P radioactivity is eluted at a volume corresponding to a molecular weight of approximately 120 000, coinciding with the colchicine binding. The remaining 32P radioactivity emerged with the void volume, indicating that it is a high-molecular-weight aggregate of the kind which is known to form with vinblastine [24]. Protein kinase activity (measured with casein as substrate) was found to emerge with a molecular weight of 54000.…”
Section: P Then Incubated With [3h]colchicine and Finallymentioning
confidence: 96%
“…Moreover, specific removal of the central pair of microtubules from sea urchin sperm tails progressively removes the colchicine-binding activity from the sperm tails and is accompanied by a corresponding increase of such activity in the extract (26) More direct evidence derives from experiments of Kirkpatrick et al (22) who showed that the major protein obtained from isolated brain microtubules characterized on the basis of ultrastructure behaves electrophoretically like the colchicine-binding protein isolated directly from brain and has the same molecular weight Furthermore, antibodies made to preparations from Tetrahymena cilia of the type that yield colchicinebinding protein appear to combine with intact bundles of microtubules (27). Using another approach, it has been shown that vinblastine-induced paracrystalline precipitates of microtubules (28)(29)(30) show in vivo radioautographic localization of eolchicine-"H (31) The isolated paracrystals also have colchicine-binding activity in vitro and have an amino acid composition similar to that reported for colchicine-bindmg protein and other presumptive microtubular subunits (32).…”
Section: Other Antimitotic Agentsmentioning
confidence: 99%